Gerenciamento do ponto de corte para a concessão de crédito no varejo brasileiro - Crespi Júnior, Hugo (2014)
One of the most important ways to finance consumers in the Brazilian market is the consumer credit offered in store. Provided by independent or captive finance companies, the consumer credit is normally granted or denied without taking into account its effect on the retailer s profitability. Denying credit to finance a high profit margin product is more damaging to the companies profits than if such refusal is about the sale of lower margin product. This suggests that there is an opportunity to improve the profitability in this sales channel. The objective of this research was to check the possibility to increase the Brazilian retailers profitability by introducing the retail products operating margin as an additional parameter of the consumer credit analysis. Simulations using tangents to ROC curves, as proposed by Stein (2005), made possible to confirm, through a new balance of type I and type II errors, that the maximization of corporate earnings occurs when using operating retail margins for determining cutoffs in consumer credit models.